Kajian Literatur Tentang Manajemen Kinerja Untuk Meningkatkan Produktivitas Organisasi - Nur Afridah; Sintia Maria Rawis; Suci Ramadhani Nalole (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
This review examines the existing literature on performance management and its impact on improving organisational productivity. Various studies show that the implementation of an effective performance management system has a significant influence on employee motivation and performance, which in turn increases organisational productivity. Important elements of effective performance management include clear goal setting, regular monitoring, constructive feedback, and rewards and incentives. In addition, employee involvement in the performance management process was also cited as an important factor in increasing their sense of belonging and commitment to the job. The review also highlighted the role of effective leadership and the utilisation of technology as important elements in successful performance management implementation. The results of this literature review suggest that a holistic approach that includes all these elements can significantly improve organisational productivity.